2021
DOI: 10.1093/plphys/kiab134
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic analysis of specific and nonspecific auxin effects on endocytosis and trafficking

Abstract: The phytohormone auxin and its directional transport through tissues are intensively studied. However, a mechanistic understanding of auxin-mediated feedback on endocytosis and polar distribution of PIN auxin transporters remains limited due to contradictory observations and interpretations. Here, we used state-of-the-art methods to reexamine the auxin effects on PIN endocytic trafficking. We used high auxin concentrations or longer treatments versus lower concentrations and shorter treatments of natural (IAA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 119 publications
5
44
0
Order By: Relevance
“…The molecular mechanism behind auxin flux sensing is unclear but could involve membrane-associated protein kinases (Hajný et al, 2020;Marhava et al, 2018;Michniewicz et al, 2007). Alternatively, we propose a second molecular mechanism for PIN polarization compatible with experimental observations (Narasimhan et al, 2021) which we refer to as 'regulator-polarizer' (Supplementary Fig. S3C-D).…”
Section: Feedback Between Anisotropic Growth and Auxin Flow Shapes Arabidopsis Root Patternsupporting
confidence: 78%
See 1 more Smart Citation
“…The molecular mechanism behind auxin flux sensing is unclear but could involve membrane-associated protein kinases (Hajný et al, 2020;Marhava et al, 2018;Michniewicz et al, 2007). Alternatively, we propose a second molecular mechanism for PIN polarization compatible with experimental observations (Narasimhan et al, 2021) which we refer to as 'regulator-polarizer' (Supplementary Fig. S3C-D).…”
Section: Feedback Between Anisotropic Growth and Auxin Flow Shapes Arabidopsis Root Patternsupporting
confidence: 78%
“…through sensing the net auxin flux through the cell (Feugier and Iwasa, 2006;Mitchison, 1980;Rolland-Lagan and Prusinkiewicz, 2005;Stoma et al, 2008), auxin concentrations (Jönsson et al, 2006;Merks et al, 2007;Smith et al, 2006;Wabnik et al, 2010), the auxin gradient inside the cell (Kramer, 2009) or a combination of those (Cieslak et al, 2015). It is also known that auxin affects endocytosis of PINs by modulating their transport (Narasimhan et al, 2021). We propose two scenarios that are compatible with this experimental observation.…”
Section: Feedback Between Anisotropic Growth and Auxin Flow Shapes Arabidopsis Root Patternsupporting
confidence: 67%
“…When auxin gradually accumulates on the lower hypocotyl side, this triggers PIN3 repolarization to the inner side of endodermal cells which (re)establishes a symmetric PIN localization and restoration of the symmetric auxin distribution across the organ, resulting in bending termination. This auxintriggered feedback on PIN repolarization requires the SCF TIR1/AFB auxin signaling (Han et al, 2020), clathrin-mediated endocytosis, GNOM-mediated trafficking, PID-mediated phosphorylation (Rakusová et al, 2016), actin cytoskeleton (Rakusová et al, 2019) and Myosin XI activity (Han et al, 2021). Such an auxin feedback mechanism ensures the fine-tuning of auxin fluxes for termination of asymmetric growth during shoot gravitropic and phototropic responses.…”
Section: Auxin Feedback On Pin Polarity To Terminate Bendingmentioning
confidence: 99%
“…For more than a decade, a central hypothesis has been that auxin inhibits endocytosis (Paciorek et al, 2005), as part of the auxin-regulated PIN polarization mechanism. However, more advanced technologies casted doubt on this model (J asik et al, 2016), which was supported by the finding that endogenous auxins are much less potent than synthetic auxin analogues (Paponov et al, 2019;Narasimhan et al, 2021). Revisiting this old question with state-ofthe-art imaging and quantification tools Narasimhan et al (2021) revealed that both natural and synthetic auxins promote PIN2 endocytosis at low concentrations, while high auxin concentrations have nonspecific effects on the endomembrane system and trafficking.…”
Section: Auxin Feedbackmentioning
confidence: 99%